Fe–Si networks in Na2FeSiO4 cathode materials. Issue 34 (15th August 2016) - Wu, P.; Wu, S. Q.; Lv, X.; Zhao, X.; Ye, Z.; Lin, Z.; Wang, C. Z.; Ho, K. M.
Abstract : Using a combination of adaptive genetic algorithm search, motif-network search scheme and first-principles calculations, we have systematically studied the low-energy crystal structures of Na2 FeSiO4 . Abstract : Using a combination of adaptive genetic algorithm search, motif-network search scheme and first-principles calculations, we have systematically studied the low-energy crystal structures of Na2 FeSiO4 . We show that the low-energy crystal structures with different space group symmetries can be classified into several families based on the topologies of their Fe–Si networks. In addition to the diamond-like network which is shared by most of the low-energy structures, another three robust Fe–Si networks are also found to be stable during the charge/discharge process. The electrochemical properties of representative structures from these four different Fe–Si networks in Na2 FeSiO4 and Li2 FeSiO4 are investigated and found to be strongly correlated with the Fe–Si network topologies. Our studies provide a new route to characterize the crystal structures of Na2 FeSiO4 and Li2 FeSiO4 and offer useful guidance for the design of promising cathodes for Na/Li ion batteries.